The Lung Alveolar Cell (LAC) miRNome and Gene Expression Profile of the SP-A-KO Mice After Infection With and Without Rescue With Human Surfactant Protein-A2 (1A0) - Thorenoor, Nithyananda; Floros, Joanna (Frontiers in Immunology, 2022)
Human SP-A1 and SP-A2, exhibit differential qualitative and quantitative effects on the alveolar macrophage (AM), including a differential impact on the AM miRNome. Moreover, SP-A rescue (treatment) of SP-A-KO infected mice impoves survival. Here, we studied for the first time the role of exogenous SP-A protein treatment on the regulation of lung alveolar cell (LAC) miRNome, the miRNA-RNA targets, and gene expression of SP-A-KO infected mice of both sexes. Towards this, SP-A-KO mice of both sexes were infected with K. pneumoniae and half of them were also treated with SP-A2 (1A0). After 6h of infection/SP-A treatment, the expression levels and pathways of LAC miRNAs, genes, and target miRNA-mRNAs were studied in both groups. We found, i) significant differences in the LAC miRNome, genes, and miRNA-mRNA targets in terms of sex, infection, and infection plus SP-A2 (1A0) protein rescue; ii) an increase in the majority of miRNA-mRNA targets in both study groups in KO males versus females and involvement of the miRNA-mRNA targets in pathways of inflammation, anti-apoptosis, and cell cycle; iii) genes with significant changes to be involved in TP-53, TNF, and cell cycle signaling nodes; iv) when significant changes in the expression of molecules from all analyses (miRNAs, miRNA-mRNA targets and genes) were considered, two signaling pathways, the TNF and cell cycle, referred to as “integrated pathways” were shown to be significant; v) the cycle pathway to be present in all comparisons made. Because SP-A could be used therapeutically in pulmonary diseases, it is important to understand the molecules and pathways involved in response to an SP-A acute treatment. The information obtained contributes to this end and may help to gain insight especially in the case of infection.